OCT in Clinical Practice: Diagnosis and Monitoring of Glaucoma and Suspected Cases - Silva, Honassys R. Rocha; Olho, Clínica do (Medical Science: Trends and Innovations Vol. 9, 2025)
Glaucoma is a leading cause of irreversible blindness, requiring a precise and multifaceted diagnostic approach. Optical coherence tomography (OCT) has become indispensable for structural assessment, yet its full potential in clinical practice remains underutilized. In this chapter, I integrate 13 years of experience and over 30,000 OCT examinations to present a protocol-based strategy that combines conventional parameters- such as retinal nerve fiber layer and ganglion cell analysis - with a differentiated focus on the anterior segment, particularly the cameral sinus, an often-overlooked structure in disease progression. By systematically incorporating anterior segment OCT (AS-OCT) into glaucoma evaluation, this approach enhances risk stratification, differential diagnosis, and treatment decisions. Case-based evidence underscores the importance of refining traditional methodologies while leveraging underexplored insights into aqueous humor dynamics and trabecular meshwork function. This work challenges conventional paradigms, demonstrating how a comprehensive, OCT-driven strategy can optimize clinical outcomes and contribute to long-term visual preservation.